Notificação da violência infanto-juvenil nas unidades de emergência em saúde: atuação e dificuldades de profissionais e serviços - Souza, Camila dos Santos (2011)
The thesis investigates the performance of health workers from the Emergency Units of the council, faced with cases of juvenile violence, considering operational difficulties in the process of identification and reporting, and describes the profile of the cases reported in the Accident and Surveillance Violence / VIVA the municipality. Studying primary data with the professionals of the Emergency lets you view demonstrations of violence, considering the constancy of the phenomenon in these services, mingling with the work process and the different interactions between professionals and clients. Moreover, to analyze the data side of the system of mandatory reporting of violence possible to know the profile of cases seen and reported in the SUS Network (Primary Care, Hospitals and polyclinics) and registered in the System VIVA Feira de Santana. The two cuts included in the study are transversal, the first with simple random sample, selected from the universe of professionals of the Public Emergency and the second clip from the total cases of children and adolescents (324 cases) and met System VIVA reported in the period 2009 and 2010 in Feira de Santana. We performed bivariate and association measures, which allowed us to determine the main procedures and difficulties in the process of notification as well as associations between characteristics of the phenomenon and profiles of victims and aggressors. Among the findings, the study revealed that professionals were the main procedures to notify the competent authorities, requesting an opinion from another professional and talk with family, in most instances cited credibility problems and revealed how the family failure, fear of involvement and lack of legal technical training in the notification process. Among children and adolescents and reported in the schedule VIVA, males predominated, with a greater frequency of occurrence in the home, violence was more common assault with injury by cutting / drilling, involving physical force, firearms and verbal threat. The other types of violence included psychological abuse, neglect and sexual offenders and most of them were women, relatives and acquaintances of the victim. It is concluded that knowledge of the epidemiology of violence, its magnitude, distribution and severity become essential to the process so to prevent and deal with effective measures and policies aimed at reducing such injuries. Thus, the increase of programs and actions directed to continued formation of the network enables the strengthening of institutions for care and protection of childhood and adolescence, as well as the expansion of trade and professional support networks, to expand the process of notification, referrals and resolution of cases.